2023
DOI: 10.1021/acsami.3c02653
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Novel High-Performance Dipolar Glass Polymer Dielectrics by Polar Rigid/Flexible Side Chains

Abstract: Developing new polymer dielectrics with superior dielectric and energy storage properties is urgent to meet the demand for electronic devices in the field of microminiaturization or harsh environments. In this paper, two dipolar glass polymers based on polynorbornene main chain and flexible/rigid cyano side chain were synthesized by ring opening metathesis polymerization method: polymer PCEMT with flexible side chains and polymer PCPMT with rigid side chains. The backbone is built from two rigid five-membered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Generally, the larger band gaps could retain higher breakdown strength in polymers. However, previous literature results indicated that in addition to the band gap, Young’s modulus and leakage current density also have an impact on the breakdown strength …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Generally, the larger band gaps could retain higher breakdown strength in polymers. However, previous literature results indicated that in addition to the band gap, Young’s modulus and leakage current density also have an impact on the breakdown strength …”
Section: Resultsmentioning
confidence: 98%
“…Meanwhile, comparing the density of states between the PPES and the PSF (Figure a), it can be noticed that PPES had a smaller LUMO energy level; therefore, the electron affinity of PPES was greater. This heightened electron affinity may limit the movement of electrons along the main chain during charge injection, resulting in significantly smaller leakage current density for PPES compared to PSF . In other words, the conduction loss of PPES was below that of PSF.…”
Section: Resultsmentioning
confidence: 99%
“…12 The large volume proportion and use of additional cooling systems due to polymer limitations are not in line with the modern design concept of light weight and efficient energy-storage capability. [13][14][15] Therefore, there is an urgent need to develop polymer dielectrics that can provide both high temperature stability and high energy storage performance.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric capacitors, as energy storage devices, offer distinct advantages including high power density, rapid charge–discharge capability, and durability. These performances make dielectric capacitors indispensable in the fields of electrical defibrillators, electrically launched weapons, and hybrid electric vehicles (HEV). However, the relatively low energy storage density ( U e ) of dielectric capacitors significantly restricts their widespread application in the mentioned fields. Commercialized biaxially oriented polypropylene (BOPP), among the most representative flexible energy storage materials, exhibits a U e of only ∼2 J cm –3 , whereas commercial electrochemical capacitors have U e 's of up to 20 J cm –3 .…”
Section: Introductionmentioning
confidence: 99%